Implementasi Aplikasi Kasir untuk Digitalisasi Transaksi Gudang Bintang Rejeki - Muhammad Shangazi; Khairunisa Khairunisa; Febrina Prihatin; Teguh Ansyor Lorosae (Universitas Pahlawan Tuanku Tambusai, 2026)
The digitalization of transaction management has become increasingly important in improving the efficiency of distribution business operations. This community service project aimed to implement a C++-based cashier application at Gudang Bintang Rejeki as a solution to manual transaction recording and inventory management. The implementation methods included observation, socialization, training, and operational assistance through a field trial approach. The application was equipped with features for transaction recording, inventory management, income and expense tracking, and QRIS-based digital payment integration. The results showed that the application improved transaction recording accuracy, accelerated data processing, simplified financial report preparation, and enabled more organized inventory management. Overall, the implementation of the cashier application contributed to improving warehouse operational efficiency and has the potential to serve as a practical digital solution for small- and medium-sized distribution businesses.